Application of the VIKOR method for solving problems in logistics - Mijalkovski Stojance; Stefanov Vasko; Mirakovski Dejan (Logistics, Supply Chain, Sustainability and Global Challenges)
When companies make strategic decisions, responsible persons must take into account as many influential parameters as possible so that the solution to the given problem is the most optimal, that is, they make the most appropriate decision. Multi-criteria decision-making (MCDM) can find a very large application for solving such very complex and important issues, where it is of particular importance that the company makes the most appropriate decision. Making the optimal decision for a given problem directly affects the financial performance of a given company.